2019
DOI: 10.1021/acsinfecdis.9b00003
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Vertical Zika Transmission: Emerging Diagnostic Approaches for an Emerged Flavivirus

Abstract: Zika virus (Zika) was recently responsible for a massive epidemic that spread throughout Latin America and beyond. Though Zika is typically asymptomatic or self-limiting, the sheer numbers of Zika infections led to the identification of unexpected phenotypes including sexual transmission, Guillain-Barrésyndrome, and teratogenicity. Thousands of infants in South, Central, and North America have now been born with microcephaly or one of a number of fetal anomalies constituting the congenital Zika syndrome (CZS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…Fetal viremia and viruria have not yet been fully described, making it difficult to predict if fetuses exposed early in pregnancy, usually the most severely affected [2,7], would still have detectable RNA at birth [9]. Additionally, the wide variety of molecular test systems used worldwide, the lack of standardization and the resulting low concordance across different platforms/laboratories, and the overall variable and low sensitivity [24,25] are important limitations of RT-PCR for the diagnosis of ZIKV congenital infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal viremia and viruria have not yet been fully described, making it difficult to predict if fetuses exposed early in pregnancy, usually the most severely affected [2,7], would still have detectable RNA at birth [9]. Additionally, the wide variety of molecular test systems used worldwide, the lack of standardization and the resulting low concordance across different platforms/laboratories, and the overall variable and low sensitivity [24,25] are important limitations of RT-PCR for the diagnosis of ZIKV congenital infection.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, compared with other congenital infections, confirmation of infant ZIKV infection remains a challenge because no available nucleic acid or serological tests have been validated for this purpose. 36 Only a proportion of infants with the typical CZS phenotype are ZIKV-positive. [37][38][39] Consequently, figures based on the detection of nucleic acids or antibodies might underestimate the true vertical transmission rate, and all ZIKV-exposed babies should be considered at risk for potential late consequences.…”
Section: Discussionmentioning
confidence: 99%
“…A single study that systematically tested infants born to ZIKV‐infected mothers estimated a 20–30% maternal–fetal transmission rate 13 . However, compared with other congenital infections, confirmation of infant ZIKV infection remains a challenge because no available nucleic acid or serological tests have been validated for this purpose 36 . Only a proportion of infants with the typical CZS phenotype are ZIKV‐positive 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Therefore, no known specific criteria are capable of identifying all cases of CZS; a combination of clinical and risk assessments, clinical knowledge, and laboratory testing to create hierarchical classes of evidence of ZIKV infection, 7 as adopted in this study, is necessary. 6 Almost all clinical and socioeconomic characteristics (except for maternal age at the beginning of a GMFM-66 score (95% confidence interval). b Significant increase in the GMFM-66 score on the second assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular tests used to detect viral genomic material are the preferred method of diagnosis because they can provide confirmed evidence of infection, according to the Centers for Disease Control and Prevention (CDC), but due to the temporal nature of ZIKV RNA in serum and urine, these tests often produce false-negative results. 6 ZIKV immunoglobulin (Ig) M antibody testing, followed by the plate reduction neutralization test (PRNT) for ZIKV, expands the diagnostic window and is recommended by the CDC in certain situations. However, it has recently been shown that negative PRNT results do not exclude the diagnosis of CZS, since among mothers who were ZIKV-positive according to qRT-PCR (real-time quantitative polymerase chain reaction), 51.5% had a negative PRNT result.…”
Section: Introductionmentioning
confidence: 99%